FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN IBU HAMIL DALAM MELAKUKAN KUNJUNGAN ANTENATAL CARE (ANC) DI BPM SYARIFAH LUBIS KOTA PADANGSIDIMPUAN - mayang wulan (ITKM WIDYA CIPTA HUSADA, 2020)
The high maternal mortality rate is caused by pregnant women ignoring the importance of the dangers in pregnancy. Antenatal care (ANC) services performed during pregnancy are very important aiming to be able to detect and manage abnormalities and complications early. Objectives this study aims to determine what factors are related to the adherence of pregnant women in conducting antenatal care visit at BPM Syarifah Lubis in the City of Padangsidimpuan. Method this type of research used an analytical survey with a cross sectional approach. The population in this study were all the number of maternal TM III with 37-40 weeks gestational age who visited antenatal care (ANC) at BPM Syarifah Lubis with 32 respondents representing this study taken by accidental techniques sampling. The results showed no relationship between age and adherence of pregnant women to antenatal care visits (ANC) (p = .082), there was a relationship between work status (p = .002) and husband support (p = .021) with adherence of pregnant women to visit Antenatal Care (ANC) at BPM Syarifah Lubis Kota Padangsidimpuan. Conclusion of this study thet there was no correlation between age and adherence of pregnant women to antenatal care visits, there was a relationship between job status and husband’s support with adherence of pregnant women to antenatal care visits at BPM Syarifah Lubis in Padangsidimpuan.